2017
DOI: 10.1097/md.0000000000007103
|View full text |Cite
|
Sign up to set email alerts
|

Application of anterior debridement and reconstruction with anatomical screw-plate fixation for lumbosacral tuberculosis

Abstract: This study aimed to determine the efficacy and safety of anterior debridement and reconstruction with anatomical screw-plate fixation in patients with lumbosacral junction tuberculosis (TB).A total of 48 patients (30 males and 18 females) diagnosed with lumbosacral junction TB were included in this study. All patients underwent surgery in our institution from January 2008 to July 2014, using anterior debridement and reconstruction with anatomical screw-plate. Outcome data were evaluated before and after surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
1
12
0
2
Order By: Relevance
“…As indicated by our results, duration of operation, blood loss, and length of hospital stay of were significantly longer in the AP group compared to the ARCH group. All measured parameters in patients using the ARCH system were also superior to results obtained from other studies on the anterior approach 10,11 . Interestingly, the ARCH group achieved similar clinical outcomes to that of the AP group.…”
Section: Discussionsupporting
confidence: 42%
“…As indicated by our results, duration of operation, blood loss, and length of hospital stay of were significantly longer in the AP group compared to the ARCH group. All measured parameters in patients using the ARCH system were also superior to results obtained from other studies on the anterior approach 10,11 . Interestingly, the ARCH group achieved similar clinical outcomes to that of the AP group.…”
Section: Discussionsupporting
confidence: 42%
“…Limited studies, however, have reported on the details of procedures using the APS. As an effective means of pedicle screw xation, APS not only provides superior postoperative spinal stability for ALIF, but allows a shorter operating time, less blood loss, and minimal posterior muscle damage [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…However, ALIF-PPS would increase the number of incision, the operating time and blood loss. While stand-alone ALIF has potential bene t of shorter operating time, less blood loss and sparing of posterior muscle damage [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Современные методы хирургического лечения туберкулезного спондилита позволяют поэтапно или одномоментно устранять деструктивные процессы в позвоночнике, проводить костно-пластическое замещение дефекта тел позвонков и восстанавливать его опороспособность [21,44,57]. Однако тактика оперативного лечения, особенно в случаях распространенных форм туберкулезного спондилита, остается предметом дискуссии.…”
Section: Discussionunclassified
“…Современные методы хирургического лечения туберкулезного спондилита подробно разработаны и включают в себя разнообразные одномоментные и этапные декомпрессивно-стабилизирующие операции на позвоночнике [8,10,44,47,48,54,57,64,65], обычно выполняемые из переднебоковых или комбинированных доступов [2,6,7,17,18,22,23,32]. Предметом дискуссий остаются выбор очередности этапов операции, использование различных вариантов задней фиксации и методик санации очага и фиксации позвоночника, в том числе из задних доступов.…”
unclassified